If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.5y + 8.4 = -20.6 Reorder the terms: 8.4 + 2.5y = -20.6 Solving 8.4 + 2.5y = -20.6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8.4' to each side of the equation. 8.4 + -8.4 + 2.5y = -20.6 + -8.4 Combine like terms: 8.4 + -8.4 = 0.0 0.0 + 2.5y = -20.6 + -8.4 2.5y = -20.6 + -8.4 Combine like terms: -20.6 + -8.4 = -29 2.5y = -29 Divide each side by '2.5'. y = -11.6 Simplifying y = -11.6
| 11z-26=-10+10z | | 2(2b-4)-3b=8-4(2-5b) | | 3x+8(2x-6)=2+14 | | A*9fora=2 | | 0.75*5x-x=8.25 | | 10a-9=43+9a | | -7(a-6)=7(a-4) | | -2z+13=45-3z | | -(4b-2)=18-2b | | 10(-5+x)-3=17 | | 3x+5x=30+6 | | -5x+14x=48+24 | | 7(x-3)+4=8x-25 | | 21u-14=0+20u | | K-2=11 | | 2=8x^4+11x^3-9x^2+15x+13 | | 4x-1=7x+9 | | 3x^3+9x^2+4x=0 | | 9(2t-6)=2(3t-9) | | -3c=15 | | 5x-15+9x=3x+29 | | 8b-7=8+13b | | 20m-20=17+19m | | 9-1c=2 | | 6x-11=6x | | 6x+12-3x-7=1 | | 16+0.17x=28+0.13x | | 39=42+x | | 6(n-6)-11n=0 | | 16+.17x=28+.13x | | -5+11x-3=25 | | 17x=3x-7 |